(untitled) (Revista Española de Fisiología, 1990)
Intracellular recording of white adipocytes was performed in an in vitro preparation. Resting potential, input resistance and membrane time constant averaged: -34 +/- 9 mV, 295 +/- 161 M omega, and 58 +/- 19 ms respectively (mean +/- SD, n = 32). Intracellular injection of positive and negative square current pulses elicited membrane voltage responses, characterized by a rectification of the voltage change evoked by positive pulses, and a slow return to baseline at the offset of hyperpolarizing pulses. The amplitude and duration of the slow return to resting potential was dependent on membrane potential, pulse duration, and extracellular K+ concentration. This response was depressed when external Ca2+ was replaced by Co2+, and by external application of 4-aminopyridine. These results indicate that white adipocytes can generate membrane voltage responses which may mostly be a consequence of the activity of ionic channels. The properties of the slow return to baseline suggest that it may be due to a transient K+ current.